Sheikh Nawawi al-Bantani’s Concept of Moral Education and Its Role in Shaping Noble Character: A Case Study at Yanisba Vocational High School, Indonesia - Haki, Ubay; Syaifuddin, Mohammad; Khozin; Misbah, Hanim (Jurnal al-Thullab, 2025)
This study aims to examine Sheikh Nawawi al-Bantani’s concept of moral education and its influence on shaping students’ noble character at SMK Yanisba Pontang, Indonesia. The research employs a qualitative approach based on library study, supplemented by field data collected through observation, interviews, and documentation. Data were analyzed using content analysis, focusing on the integration of Sheikh Nawawi’s principles into school practices. Findings indicate that moral education is implemented through routine programs, such as congregational prayers, recitation of moral texts, and discipline reinforcement via school regulations. Teacher role-modeling and behavioral habituation proved effective in cultivating moral awareness and producing tangible changes in student attitudes, including discipline, responsibility, politeness, and mutual respect. Theoretically, this study reinforces Sheikh Nawawi’s principles, particularly uswah hasanah (teachers as role models) and tadrib al-nafs (training oneself through habituation). The results emphasize that moral internalization requires practical engagement and consistent repetition of virtuous behavior. Practically, this model can be applied in vocational schools to develop students with strong moral and spiritual character, preparing them to face social and professional challenges effectively.